1999
DOI: 10.1177/088307389901401113
|View full text |Cite
|
Sign up to set email alerts
|

Factor V1691 G-A, Prothrombin 20210 G-A, and Methylenetetrahydrofolate Reductase 677 C-T Variants in Turkish Children With Cerebral Infarct

Abstract: Inherited gene defects related to the coagulation system have been reported as risk factors for ischemic stroke. These gene defects include a G-A transition at nucleotide 1691 in exon 10 of the Factor V gene causing activated protein C resistance; a G-A transition in the 3' untranslated region of the prothrombin gene at nucleotide position 20210 (G-A), which is associated with increased levels of prothrombin activity; and a C-T polymorphism at nucleotide 677 in the methylenetetrahydrofolate reductase gene resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 18 publications
3
33
0
1
Order By: Relevance
“…who were t-MTHFR homozygotes in a Turkish childhood stroke population and no difference in frequency from control individuals (Akar et al 1999). On the other hand, Cardo and colleagues (2000) found that nearly 30% of Spanish children with stroke were t-MTHFR homozygotes, twice as many as the control population, although this did not achieve statistical significance and the relation with homocysteine levels was not clear.…”
Section: Homozygous Heterozygous Negative T-mthfr T-mthfr T-mthfrmentioning
confidence: 93%
“…who were t-MTHFR homozygotes in a Turkish childhood stroke population and no difference in frequency from control individuals (Akar et al 1999). On the other hand, Cardo and colleagues (2000) found that nearly 30% of Spanish children with stroke were t-MTHFR homozygotes, twice as many as the control population, although this did not achieve statistical significance and the relation with homocysteine levels was not clear.…”
Section: Homozygous Heterozygous Negative T-mthfr T-mthfr T-mthfrmentioning
confidence: 93%
“…This mutation has been shown to be the most prevalent hereditary cause of venous thrombosis [28]. However, the roles described for MTHFR in arterial vascular disease and particularly cerebrovascular disease are contradictory [2,16,17,21,[29][30][31][32][33]. Lopaciuk et al [17] from Poland reported that homozygosity for C677T mutation in the MTHFR gene is not associated with an increased risk for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma levels of homocysteine have been established as a risk factor for vascular disease [16]. MTHFR (EC 1.5.1.20) involved in folate metabolism catalyzes the formation of 5-methylentetrahydrofolate from 5,10-methylentetrahydrofolate, which is the predominant circulatory form of folate and a carbon donor for remethylation of homocysteine to methionine [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings, the increase in platelet activation, apoptosis, oxidative status (MDA), aggregation, altered platelet membrane binding features, and decreased platelet nitrite levels in hyperlipidemia might elevate thrombotic risk causing atherogenesis to progress. New risk assessment criteria for thrombosis and cardiovascular diseases [42,43] and new drugs [44,45] for inhibition of coagulation are very important research areas. Clopidogrel is a drug that has been used for the secondary prevention of atherothrombotic events related to ischemia [46].…”
Section: Discussionmentioning
confidence: 99%